Kepuasan Hidup Pada Muslim Minoritas Di Perbatasan Indonesia-Filipina - Macpal, Sunandar; Apita, Aykal Y (LPPM IAIN Sultan Amai Gorontalo, 2021)
The Sangihe Islands, a region on the border between Indonesia and the Philippines, offer an intriguing context for understanding the lives of minority communities, particularly Muslims, in relation to their life satisfaction. This study aims to describe how life satisfaction is experienced by Muslim minorities in Sangihe and how these minorities interpret their lives. The research utilizes ethnographic methods as part of qualitative research with a phenomenological approach to gain a comprehensive understanding of the lived experiences of informants. The findings of this study suggest that the life satisfaction of Muslim minority communities on the Indonesia-Philippines border is not only determined by economic factors but also by the quality of social relationships, diversity, and religious practices.